Risk of heart disease in relation to radiotherapy and chemotherapy with anthracyclines among 19,464 breast cancer patients in Denmark, 1977-2005 - Rehammar, J; Jensen, M; McGale, P; Lorenzen, E; Taylor, C; Darby, S; Videbæk, L; Wang, Z; Ewertz, M (Elsevier, 2017)
BACKGROUND AND PURPOSE: The risk of heart disease subsequent to breast cancer radiotherapy was examined with particular focus on women receiving anthracycline-containing chemotherapy. MATERIAL AND METHODS: Women diagnosed with early-stage breast cancer in Denmark, 1977-2005, were identified from the register of the Danish Breast Cancer Cooperative Group, as was information on cancer-directed treatment. Information on heart disease was sought from the Danish National Patient and Cause of Death Registries. Incidence rate ratios were estimated comparing left-sided with right-sided cancer (IRR, LvR), stratified by calendar year, age, and time since breast cancer radiotherapy. RESULTS: Among 19,464 women receiving radiotherapy, the IRR, LvR, was 1.11 (95% CI 1.03-1.20, p=0.005) for all heart disease and among those also receiving anthracyclines the IRR, LvR, was 1.32 (95% CI 1.02-1.70, p=0.03). This risk was highest if the treatment was given before the age of 50years (IRR, LvR, 1.44, (95% CI 1.04-2.01) but there was no significant trend with age or time since treatment. CONCLUSIONS: Radiotherapy for left-sided breast cancer is associated with a higher risk of heart disease than for right-sided with the largest increases seen in women who also received anthracycline-containing chemotherapy.